Constructing Sappho: refiguring the eroticism of Sappho’s poetry in eighteenth-century English translation - Lander, Harriet Elwell (2019)
This thesis explores how Sappho’s eroticism was constructed in the eighteenth-century through English translation. The eight books of translation which first appear in the period 1685 – 1760 form the basis of this research, which examines the ways in which the eroticism of Sappho was constructed as heteroromantic by the early translators. Sappho was largely seen as a poet who wrote heteroerotic poetry, even though her received biography and reception discusses her homoerotic attributes. Receptions of Sappho usually take an approach which covers material that is not a translation, and this thesis seeks to redress that balance by examining the first translations of Sappho for an English reading audience. The methodology draws on reception studies and translation studies theory, as well as book history. The book itself forms the basis for constructing Sappho through reading, and the way in which the translated text of Sappho is presented can dramatically alter how readers approach the translated text. There is a small amount of classical material to work with. In each book there is at most ten poems printed, and as little as one poem. Therefore, the choices that each translator makes within their texts, and the ways in which the text is presented make dramatic changes to how Sappho’s eroticism was viewed. The books are analysed as individual pieces, but together form a more nuanced view of how Sappho’s eroticism was constructed in this period. This is a book-centred approach to the material, and there are three strands to this study. The first is transmission, the second is paratext and the third is translation choices. Together, in each translation, critical discussion of these aspects build on each other to illustrate a translator or editor’s viewpoint on Sappho’s eroticism in her persona and her poetry. By moving away from ideas of receptions of Sappho which are focussed around her use in high culture such as fine art or poetic receptions, or popular culture or subculture such as fashion or fandoms, and looking at the reception of Sappho through translations opens up the possibility for a different kind of Sapphic reception. This thesis explores how through translation, ideas of Sappho’s eroticism were being deliberately constructed by those who were making her work available for an English-reading audience.